Performance evaluation and characteristics of selected tube wells in the Coastal Alluvium Aquifer, Selangor - Jusoh, Mohd Fauzie; Mohamed Zawawi, Mohamed Azwan; Che Man, Hasfalina; Mohammed, Thamer Ahmed (Universiti Putra Malaysia Press, 2014)
Alluvial aquifers can be found in most of the coastal areas of Peninsular Malaysia. Seven tube wells located in such aquifers in the west coast of Selangor state had their performance evaluated by carrying-out step drawdown tests. The performance of these wells was evaluated in terms of aquifer loss, well loss, specific capacity and well efficiency. The aquifer loss coefficient and well loss coefficient were found to be in the range of 0.0198 hrm-2 to 0.4014 hrm-2 and from 0.0001 hr2m-5 to 0.0410 hr2m-5, respectively. The drawdown in tube wells TW1 and TW7 is mainly influenced by well loss component as compared to the aquifer loss component, while in tube wells TW2, TW3, TW4, and TW5, the drawdown is mainly influenced by aquifer loss component. The drawdown in tube well TW6 is influenced by aquifer loss component at a low discharge rate, but at high discharge rate, it is influenced by well loss component. The specific capacity and efficiency of the tested tube wells varied from 1.329 m2hr-1 to 40.166 m2hr-1, and from 11% to 96%, respectively. Tube wells TW2 and TW4 are categorized as high productive wells, while tube wells TW1, TW3, TW5 and TW7 are categorized as moderate productive wells and tube well TW6 as low productive well.